Role of civil society organizations for promoting green and blue infrastructure to adapting climate change: Evidence from Islamabad city, Pakistan. (1st August 2021) - Mumtaz, Muhammad
Abstract: This study contributes to understand the role of the civil society organizations (CSOs) for promoting the green and blue infrastructure (GBI) by studying the case of Islamabad city. Pakistan is facing severe crises of changing climate and it is ranked one of the most vulnerable countries due to climate change. Adaptation to climate change is the main strategy of Pakistan to deal with climatic impacts. Implementing the GBI plays a key role in urban areas for promoting adaptive governance towards climate change. Many efforts have been initiated to manage the issue of climate change by the national, provincial, and local governments in Pakistan. The latest and notable strategy by Pakistani government was devised in the form of the Clean Green Pakistan Strategy (CGPS) to promote the GBI as adaptation strategy to address climate change. However, there are multiple challenges and hurdles for effective implementation of the CGPS. On the heels of Paris Agreement 2015, the CSOs have growing role to overcome such challenges and to prepare the local communities in collaboration with local institutions especially in cities for advancing the GBI and tackling climate change effectively. This study is conducted to understand and uncover the role of the CSOs for promoting the GBI as adaptive strategy in dealing with climate change in Islamabad city of Pakistan. The study focuses to investigate and dig out the prominent initiatives of the CSOs towards the GBI in Pakistani governance system. It also identifies the hurdles and challenges for the CSOs in relation to promote the GBI in Pakistan. A case study approach as research methodology is employed where semi-structured interviews were conducted with relevant actors in Islamabad city. The study finds that the CSOs are actively involved in promotion of the GBI in collaboration with Islamabad administration through plantation drive, educating school students on the GBI, arranging training programs for the local community, providing advocacy assistance and helping the city government for establishing policies and action plans for the GBI. The CSOs act as representative of the local community in devising the GBI policies and implementation actions at local scale through consistent engagements with the local administration and the local community in the city. The CSOs have emerged as a mediator in aligning intergovernmental relations for implementing the GBI as the CSOs are closely working with local, provincial, and federal institutions, thus they are key for all tiers of the government. The major challenges faced by the CSOs are identified: weak linkage and cooperation among local and international organizations, limited financial resources, and weak capacity of local organizations. The role of the CSOs appears in an infancy stages but it is emerging with a reasonable pace for effective adaptive governance in relation with the GBI in Pakistan.